Impact damage mitigation using bioinspired CFRP laminate architectures - Amorim, Luís Manuel Machado (2019)
Carbon fibre reinforced polymers (CFRP) are widely used in advanced applications due to their high performance and low weight. However, when exposed to some conditions, as shear, dynamic and impact loading, they may develop interlaminar damages. One of the most common and dangerous solicitations that they must face in service is low velocity impact (LVI) events. To improve damage tolerance to LVI events, three new bioinspired CFRP laminates were developed and tested in the present work to assess and compare their behaviour to the one presented by a typical aeronautic standard laminate. All these studied laminates, having approximately the same thickness of 4 mm, were produced by vacuum bag infusion and observed under deflexion and scanning electron microscopes (SEM) for assessing their processing quality. Interlaminar shear strength (ILSS) and LVI tests were performed in order to evaluate their delamination resistance and impact response. LVI tests were performed for all laminates at the three different impact energy levels of 13.5 J, 25 J and 40 J. Those tests have shown that the bioinspired hybrid laminate (HYB) and all bioinspired ones presented higher interlaminar shear strength and energy absorption for the 40 J impact energy than the standard CFRP laminate (LS), respectively.